Shrimp Cassava Cracker Puffed by Microwave Technique: Effect of Moisture and Oil Content on Some Physical Characteristics - Nguyen, Thao Thanh; Le, Tuan Quoc; Songsermpong, Sirichai (Agriculture and Natural Resources, 2013)
Low-fat products have been proposed as a substitute for deep fried foods due to their improved shelf life and as a response to consumers’ health concerns with fried foods. Microwave puffing was used to puff shrimp cassava cracker (SCC) as a substitute for deep fried SCC in this study. The dried semiproduct with various levels of initial moisture content (IMC) from 16 to 31.5% on a wet basis and added oil percentage (AOP) from 0 to 21% by weight were puffed by microwave heating for 1 min. Deep oil fried SCC was also used in comparison tests of hardness, volume expansion and sensory evaluation. It was clear that after microwave puffing, the hardness and volume expansion were significantly different at various levels of IMC and AOP. At the suitable IMC, the hardness of SCC without oil was noticeably higher than that of the sample with oil whereas its volume was significantly higher. The AOP had a negative correlation with hardness and volume expansion (%) at a highly significant level (P < 0.01). Hardness and volume expansion had a positive correlation at P < 0.05. The optimum level of IMC for volume expansion of SCC was 21.5% on a wet basis and an AOP at 15% and these could reduce the hardness comparable to the fried SCC. Although the volume expansion of microwave SCC was less than that of fried SCC, the sensory evaluation indicated that microwave heating at the optimum conditions was acceptable by the panelists as a new technique for puffed SCC product, especially in terms of avoiding high oil content.